2008
DOI: 10.1117/1.2967986
|View full text |Cite
|
Sign up to set email alerts
|

Imaging pulsatile retinal blood flow in human eye

Abstract: Abstract.A functional Fourier domain optical coherence tomography instrument offering spectral Doppler imaging of in vivo pulsatile human retinal blood flow was constructed. An improved phase-resolved algorithm was developed to correct bulk motion artifacts. Spectral Doppler imaging provides complementary temporal flow information to the spatially distributed flow information of the color Doppler image by providing direct visualization of the Doppler spectrum of the flow whose pattern can be further quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…However these methods increase the computational complexity and time. The correction may also introduce artifacts when the blood vessels are large and take most of the pixels for an A-line [35,45]. We have shown that the Doppler variance method is not sensitive to bulk-motion and the method can be used without correcting the bulk-motion when the sample-movement-induced velocity changes gradually [42].…”
Section: Bulk-motion and In-vivo Imagingmentioning
confidence: 96%
See 3 more Smart Citations
“…However these methods increase the computational complexity and time. The correction may also introduce artifacts when the blood vessels are large and take most of the pixels for an A-line [35,45]. We have shown that the Doppler variance method is not sensitive to bulk-motion and the method can be used without correcting the bulk-motion when the sample-movement-induced velocity changes gradually [42].…”
Section: Bulk-motion and In-vivo Imagingmentioning
confidence: 96%
“…Although this correction artifact is not important in most imaging areas, the artifacts may cause erroneous blood vessel locations in the color Doppler image in regions with large blood vessels such as the optic disk. An improved phase-resolved algorithm has been proposed to correct this artifact [45]. Although effective, the improved algorithm increases the calculation time.…”
Section: Bulk-motion and In-vivo Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…However measurement of the absolute blood flow is still a challenge because of its pulsatile nature. Doppler optical coherence tomography (OCT) enables the imaging of retinal blood velocity in human eyes [7,8]. The principle of Doppler OCT is based on measuring the Doppler shift caused by the moving blood cells relative to the OCT probing light.…”
Section: Introductionmentioning
confidence: 99%